Effect of Viscosity on the GTA Welds Bead Penetration in Relation with Surface Tension Elements - Touileb, K.; Djoudjou, R.; Ouis, A. (Engineering, Technology & Applied Science Research, 2016)
The aim of this paper is to study the effect of the viscous dissipation on the surface tension and its role on the shape of weld pool. Experiments were conducted on four different casts of ferritic stainless steel with different content in the sulfur and titanium. The results show in particular that the presence of titanium solid compounds affects the role of sulfur as surfactant element. Titanium in the presence of carbon and oxygen, titanium forms solid compounds which affect the Marangoni convection due to the sulfur element in the weld pool. The viscous dissipation due to these compounds alters the flow rate of the molten metal. We expect that the viscosity of metal liquid was altered by these solid compounds. The viscous dissipation due to these compounds contributes to heat the molten metal leading to larger weld bead.